Spowiedz pamieci ; Proba swiatla : opowiadnia - Kuriata, Czeslaw, 1938-; Kuriata, Czeslaw, 1938- (Olsztyn : Pojezierze, 1985., 1985)
Selected contemporary short stories about the home life.
Keywords: Short stories, Polish